Thai undergraduate science, technology, engineering, arts, and math (STEAM) creative thinking and innovation skill development: a conceptual model using a digital virtual classroom learning environment - Wannapiroon, Naphong; Pimdee, Paitoon (My University, 2022)
Qualitative and quantitative research methods were undertaken to examine and develop a digitally based virtual classroom learning environment (VCLE) for Thai undergraduate students’ creative thinking and innovation enhancement in science, technology, engineering, arts, and math (STEM/STEAM) disciplines. The research methodology was divided into two phases, including the synthesis and then the design of the VCLE. Also, in addition to the study’s authors, nine experts were used for the model’s development and another ten for its assessment (19 total). From their in-depth interviews and subsequent content analysis, their input of the proposed STEAM-ification process was synthesized and the data analyzed. The results revealed that the VCLE design should begin with a face-to-face, classroom learning environment in which the ‘gamification’ mechanisms were introduced and examined. This was then reinforced by moving the gamification process online outside of the classroom. Furthermore, five VCLE STEAM-ification steps were found to be particularly useful for enhancing creative thinking and student innovation. These included investigation, discovery, connections, creativity, and reflection. Moreover, we identified the gamification process as consisting of three main components. These were the ‘game mechanics,' the ‘game dynamics,' and ‘player emotions’. The ten experts agreed that the VCLE STEAM-ification creativity and innovation (C & I) process was appropriate at an ‘excellent’ level (x¯ = 4.68, S. D. = 0.47), which has great potential in the development of Thai undergraduate student C & I skills. Also, when undertaken correctly, innovation and motivation to learn are also outcomes from both VCLE and gamification applications. Thus, when students undertook study with the VCLE STEAM-ification format, they were found to achieve higher levels of creativity and innovation than students who studied using the traditional teaching plan. These results were found to be statistically significant at the.01 level.
Keywords: 21st Century education; Creative Thinking; Critical thinking; Digital Learning Environment; Gamification; Innovation skills; STEAM-ification; STEM; Thailand